Advancing a social justice agenda in health professions education - Jacobs, Cecilia; Van Schalkwyk, Susan; Blitz, Julia; Volschenk, Mariette (Critical Studies in Teaching and Learning, 2023)
Health Professions Education (HPE) curricula have a dual purpose: to deliver professionals who are clinically competent and critically conscious of the contexts and health systems they serve. This qualitative study advances a social justice agenda by exploring the range of understandings that HPE teachers have of this dual purpose of their curricula. Thirty-four respondents participated in eleven focus groups and eleven interviews. Data were analysed thematically. While participants understood this dual purpose of their curricula, some felt that clinical competence should be emphasised above critical consciousness. Implementing curricula that develop critically conscious graduates raises questions about what counts as knowledge, and about how far our responsibility extends in preparing students to become change agents. This has implications for the role and identity of the HPE teacher and points to a re-envisioning of the process of curriculum development and the role that HPE centres play in the process of curriculum development.